Trends and relationship between chlorophyll-a and sea surface temperature in the central equatorial Indian Ocean. Issue 11 (1st November 2016) - Kumar, G. Shiva; Prakash, Satya; Ravichandran, M.; Narayana, A.C.
ABSTRACT: This work presents the trend analysis and relationship between chlorophyll- a (chl- a ) concentration and sea surface temperature (SST) in the central equatorial Indian Ocean (CEIO) using Aqua MODIS chl- a Level-3 Standard Mapped Image (SMI) data for a period of 10 years (2002–2012). In order to understand the monsoonal variability of chl- a concentration and SST and to evaluate their relationships over the CEIO, trend analysis of chl- a values was carried out. The area average chl- a concentration in the region shows a weak annual cycle with high concentration during winter (October–December) and low in summer (June). High chl- a concentration (~0.22 mg m −3 ) is observed during early winter in the region. Chl- a concentration starts decreasing from March onwards until the onset of summer monsoon. The data reveal low chl- a concentrations during summer period, i.e., from June to September, which is in accordance with several observations, and higher concentrations during October to December. The other reason is that satellite sensor may not capture chl- a variability more accurately because of cloud cover during summer monsoon time. A reasonably significant coefficient of determination ( R 2  = 0.51; significant at p  < 0.05 level) between SST and chl- a concentration is recorded. This study clearly suggests that the SST acts as a proxy for variables which cause high chl- a concentration in the CEIO.